Equality and tradition : questions of value in moral and political theory - Scheffler, Samuel, 1951- (Oxford University Press, 2010)
This collection of essays by noted philosopher Samuel Scheffler combines discussion of abstract questions in moral and political theory with attention to the normative dimension of current social and political controversies. In addition to chapters on more abstract issues such as the nature of human valuing, the role of partiality in ethics, and the significance of the distinction between doing and allowing, the volume also includes essays on immigration, terrorism, toleration, political equality, and the normative significance of tradition. Uniting the essays is a shared preoccupation with questions about human value and values. The volume opens with an essay that considers the general question of what it is to value something - as opposed, say, to wanting it, wanting to want it, or thinking that it is valuable. Other essays explore particular values, such as equality, whose meaning and content are contested. Still others consider the tensions that arise, both within and among individuals, in consequence of the diversity of human values. One of the overarching aims of the book is to illuminate the different ways in which liberal political theory attempts to resolve conflicts of both of these kinds.